Dysfunctions in Promotions Managers from Lodz Comapanies on the Selected Examples - Syper-Jędrzejak, Marzena (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
This article presents the question of dysfunction within the managerial promotions. Based on literature studies and the research problem areas in the field of promotion policy were identified. Of particular note are the criteria for promotion, and integration of the promotion policy with of personnel policy and company's strategy. These areas are a source of potential problems with the maintenance of valuable human resources in the company.